DETERMINAN FAKTOR – FAKTOR BERKAITAN DENGAN KEJADIAN OBESITAS PADA ORANG DEWASA USIA 30 – 50 TAHUN DI KECAMTAN GAJAHMUNGKUR, KOTA SEMARANG - Nurul Hasna Zulfannisa; J Supadi; Yuniarti Yuniarti (Poltekkes Kemenkes Semarang, 2018)
Background : School age is a child growth period, so need to pay attention to nutrients and foods consumed safely. The adverse effects of consuming unhealthy and unsafe snack foods in schools need to be avoided, this can be done through health promotion. One of the ways in which students are not saturated in extension activities is to use puzzle games because the delivery of nutritional messages becomes more fun and involves participating students actively in the game.Objective : To know the effectiveness of nutritional education with the media of puzzle to the knowledge, attitude, and practice of students related to snack food at SDN Tlogosari Kulon 02 and SD N Pedurungan Lor 1.Method : This research type is Quasi Experiment with design time series design. Sampling using random sampling technique to get 30 treatment samples and 30 control samples. Data collected are knowledge, attitude and practice data. The statistical tests used Paired t-test, Wilcoxon, independent t-test and Mann Whitney test.Result : There was a difference of knowledge and attitude of treatment group after giving education with puzzle media (p = 0,000, p = 0,030). There were no differences in practice in the treatment group and the control group after the intervention (p = 0.492 and p = 0.203). There is a significant difference of knowledge and attitude between treatment and control group (p value = 0,011; p value = 0,016). There was no significant difference in practice between treatment and control groups after intervention (p value = 0.152).Conclusion : The provision of nutritional education with puzzle media can improve knowledge and attitude of students about food snack.